Propuesta de modificación de políticas públicas con el fin de evitar la sobrepoblación penitenciaria en Costa Rica - Salazar, Alonso (2016)
It is quite clear that the prison system of our country is going through a crisis. Prison overcrowding results in a violation of a number of human rights, and urgent measures are required to solve such problem. This article presents three specific ideas related to legal and budgetary reforms.